MISAPPLICATION OF GEOGRAPHICAL INDICATION RULES IN INDONESIAN LOCAL PRODUCTS: Penyalahgunaan Implementasi Aturan Indikasi Geografis Dalam Produk Lokal Indonesia - Siregar, Raja Koresy Melkisedek; Priskila Lambasa Septuagesima Siregar; Raja Yosia Manahan Trinitas Siregar (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2024)
Indonesia own a lot of rich variety of natural resource, ranking 2nd in globa Variety Index in 2022, But the more varied the natural resources, the more accurate regulation the nation needed to ensure the benefit of ts natural resources to be given to the local organizer and the people, in which is regulated in Statute no 20, Year 2016 about Trademark and Geographical Indication. Geographical Indication itself has its definition as a mark that show the origin of the local product as being influenced and inseparable by geographical factor, giving certain reputation and quality to its local product like White Pepper muntok or Sumbawa Honey in which included in this category as one. However, there’s a misuse of corporation/people that use the benefit of Geographical Indication’s mark without the requirement of it, resulting of the local people in loss and worsen their economical condition. Data shows that there’s 138 product registered as Geographical Indication by the Directorate General of Intellectual Property (DJKI),yet some of them are not qualifed as one within the statute, in which resulting to unhealty rivalry between different local products as well. Significant measure are needed to ensure justice is upheld to protect local product so the people can be able to enjoy the benefit of natural resource in their area.